Pengaruh Employee Engagement Dan Lingkungan Kerja Terhadap Motivasi Kerja Karyawan Di Divisi Human Capital Management Bank Xyz - Christy Kristanti dan Anas Lutfi (Universitas Tarumanagara, 2019)
The purpose of this research is toexamine wether Employee Engagement and Work Environment can influence Work Motivation. The populations of this research are employeeat Bank XYZ and the samples are employee in Human Capital Management Division.Number of employee in Human Capital Management is 156 employees. The samples are collected from 148 respondents by online questionnaires with the non probability sampling technique with purposive sampling method. The analysis technique used is multiple linear regression with supported application SPSS 23 version. The result from data analyze showed that Employee Engagement affectedWork Motivation.